2016
DOI: 10.1080/2162402x.2015.1105429
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic adenoviruses coated with MHC-I tumor epitopes increase the antitumor immunity and efficacy against melanoma

Abstract: The stimulation of the immune system using oncolytic adenoviruses (OAds) has attracted significant interest and several studies suggested that OAds immunogenicity might be important for their efficacy. Therefore, we developed a versatile and rapid system to adsorb tumor-specific major histocompatibility complex class I (MHC-I) peptides onto the viral surface to drive the immune response toward the tumor epitopes. By studying the model epitope SIINFEKL, we demonstrated that the peptide-coated OAd (PeptiCRAd) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
97
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(102 citation statements)
references
References 41 publications
4
97
0
1
Order By: Relevance
“…Although shielding of HAdv with PEG effectively prevents virus neutralization by preexisting neutralizing antibodies, allowing for repeated gene delivery in a gene transfer or vaccination setting [132,133], the utility of this approach in other applications has limitations. Specifically, although shielding oncolytic HAdv with PEG or protein conjugates significantly increases the efficacy of oncolytic HAdvbased vectors in mouse models [130,132], after the initial round of replication, the progeny of oncolytic virus produced in tumor sites would not be covered with PEG or protein shields, thus exposing the virus to receptors and cells of the innate immune system. Moreover, certain cytokines, most notably IL-6 and IL-12, still remain elevated after systemic delivery [134] or direct blood cell exposure to PEGylated HAdv vectors [48], demonstrating that any single-pronged approach to avoiding virus recognition by the innate immune system is unlikely to prevent or alleviate all factors and mechanisms responsible for triggering multifaceted host innate immune and inflammatory responses to HAdv.…”
Section: Complexity Of Designing Hadv Vectors With Reduced Innate Immmentioning
confidence: 99%
“…Although shielding of HAdv with PEG effectively prevents virus neutralization by preexisting neutralizing antibodies, allowing for repeated gene delivery in a gene transfer or vaccination setting [132,133], the utility of this approach in other applications has limitations. Specifically, although shielding oncolytic HAdv with PEG or protein conjugates significantly increases the efficacy of oncolytic HAdvbased vectors in mouse models [130,132], after the initial round of replication, the progeny of oncolytic virus produced in tumor sites would not be covered with PEG or protein shields, thus exposing the virus to receptors and cells of the innate immune system. Moreover, certain cytokines, most notably IL-6 and IL-12, still remain elevated after systemic delivery [134] or direct blood cell exposure to PEGylated HAdv vectors [48], demonstrating that any single-pronged approach to avoiding virus recognition by the innate immune system is unlikely to prevent or alleviate all factors and mechanisms responsible for triggering multifaceted host innate immune and inflammatory responses to HAdv.…”
Section: Complexity Of Designing Hadv Vectors With Reduced Innate Immmentioning
confidence: 99%
“…It was already reported that the complex presented good stability and no significant decrease of zeta potential was observed 15, 30, and 45 minutes after incubation in the same conditions (MilliQ water ph 7.4). Moreover, no aggregation was seen at these time points (14). First, the electric surface charge (zeta potential) of the complex was analyzed to see whether the addition of the Carnosine6K was influencing the charge and the size of the adenovirus-carnosine complex (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PeptiCRAd, нагруженные эпитопами опухолевых антигенов -TRP2 и gp100 -умень-шают рост как инъецированной опухоли, так и вторичных необработанных меланом. В мыши-ной ксенографтной модели меланомы человека PeptiCRAd, несущий эпитопы MAGE-A1 и экс-прессирующий GM-CSF, увеличил долю CD8 + Т-лимфоцитов, специфичных к MAGE-A1, и вызывал регрессию опухолей [13]. Для обе-спечения адресной доставки, например в слу-чае, когда инъекция внутрь опухоли затруднена, можно использовать для доставки онколитиче-ских вирусов инфицированные клетки, напри-мер мезенхимные стволовые клетки, обладаю-щие опухолетропностью, как это было показано для вируса Delta24-RGD.…”
Section: Nepomnyashchikh Ts Et Al непомнящих тс и др Medical Imunclassified